2011
DOI: 10.1371/journal.pone.0023360
|View full text |Cite
|
Sign up to set email alerts
|

A Booster Vaccine Expressing a Latency-Associated Antigen Augments BCG Induced Immunity and Confers Enhanced Protection against Tuberculosis

Abstract: BackgroundIn spite of a consistent protection against tuberculosis (TB) in children, Mycobacterium bovis Bacille Calmette-Guerin (BCG) fails to provide adequate protection against the disease in adults as well as against reactivation of latent infections or exogenous reinfections. It has been speculated that failure to generate adequate memory T cell response, elicitation of inadequate immune response against latency-associated antigens and inability to impart long-term immunity against M. tuberculosis infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 35 publications
4
34
0
4
Order By: Relevance
“…2 and 4). In agreement with our results, Dey et al also observed induction of IL-2 + TNFα + IFNγ + and IL-2 + TNFα + CD4 T cells after boosting BCG with a DNA-vaccine encoding α-crystallin (Rv2031c) [32], and boosting BCG with the MVA-vector expressing Ag85A also resulted in increased numbers of polyfunctional CD4 T cells with similar phenotypes as observed in the present study [33]. However, regarding the protective role of IL-2 + TNFα + IFNγ + T cells against M.tb infection there have been conflicting results [25], [33], [34], [35], [36].…”
Section: Discussionsupporting
confidence: 93%
“…2 and 4). In agreement with our results, Dey et al also observed induction of IL-2 + TNFα + IFNγ + and IL-2 + TNFα + CD4 T cells after boosting BCG with a DNA-vaccine encoding α-crystallin (Rv2031c) [32], and boosting BCG with the MVA-vector expressing Ag85A also resulted in increased numbers of polyfunctional CD4 T cells with similar phenotypes as observed in the present study [33]. However, regarding the protective role of IL-2 + TNFα + IFNγ + T cells against M.tb infection there have been conflicting results [25], [33], [34], [35], [36].…”
Section: Discussionsupporting
confidence: 93%
“…These results suggested that BCG/ DNA vaccination might be a potential candidate since it was able to generate a much prolonged Th1 immune response when compared with BCG and BCG+ P groups. As many previous studies demonstrated a positive correlation between Th1 immune response and protection [15,50,51], we infer that the improved Th1 immune response elicited by the BCG prime/DNA boost strategy may result in a stronger protection than other groups in this study; however, it still needs to be confirmed by further studies. For future studies, we are planning to develop a viral-based vaccine and rBCG expressing Rv0577 protein, then use subunit vaccines to boost rBCG and to evaluate the protective efficacy and safety of this promising vaccines.…”
Section: Discussionmentioning
confidence: 48%
“…Although DNA vaccines are traditionally considered as the priming vector in the design of vaccine strategies, DNA-based anti-TB vaccines are often used to boost BCG since the majority of the human population is already BCG-vaccinated. Numerous reports show that BCG prime-DNA vaccination boost regimens in mice enhance protective efficacy against M. tuberculosis infection compared to BCG vaccination alone [6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic of DNA vaccination offers great advantage in the design of vaccines against intracellular pathogens such as Mycobacterium tuberculosis (M. tuberculosis), since it is believed that efficient induction of Th1 CD4 T cell immunity is crucial to the deference against M. tuberculosis [5]. Accordingly, although DNA vaccines have traditionally been regarded as priming vectors, it is reported that DNA vaccines also act as effective boosters of anti-TB cellular immunity that has been primed by BCG [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%